Influence of bundled care treatment on functional outcome in patients with intracerebral hemorrhage - Mrochen, Anne; Song, Yu; Harders, Verena; Sembill, Jochen A.; Sprügel, Maximilian I.; Hock, Stefan; Lang, Stefan; Engelhorn, Tobias; Kallmünzer, Bernd; Volbers, Bastian; Kuramatsu, Joji B. (Frontiers in Neurology, 2024)
Background and Aims: General guideline-recommendations in patients with intracerebral hemorrhage(ICH) include blood pressure-, temperature-and glucose management. Therapeutic effect of such a "care bundle" (blood pressure lowering, glycemic control, treatment of pyrexia) on clinical outcomes becomes increasingly established. For the present study we aimed to investigate associations of strict bundled care treatment(BCT) with clinical outcomes and to characterize associations with key outcome effectors such as hematoma enlargement(HE) and peak perihemorrhagic edema(PHE).We screened consecutive ICH patients(n=1,322) from the prospective UKER-ICH cohort study. BCT was defined as achieved and maintained therapeutic ranges for systolic blood pressure(110-160mmHg), glucose(80-180mg/dl), and body temperature(35.5-37.5°C) over the first 72hours. The primary outcome was functional outcome at 12months(modified Rankin Scale(mRS) 0-3), secondary outcomes were mortality at 12months, occurrence of hematoma enlargement, and development of peak perihemorrhagic edema. Confounding was addressed by doubly-robust methodology to calculate absolute treatment effects(ATE) and calculation of e-values.Results: 681 patients remained for analysis, 182 patients fulfilled all three BCT criteria and were compared to 499 controls. The ATE of BCT to achieve the primary outcome was 9.3%,95%CI(1.7 to 16.9),p<0.001;e-value:3.1,CI(1.8). Mortality at 12months was significantly reduced by BCT(ATE:-12.8%,95%CI(-19.8 to -5.7),p<0.001;e-value:3.8, CI(2.2), no association was observed for HE or peak PHE. Significant drivers of BCT-effect on the primary outcome were systolic blood pressure control(ATE:15.9%) and maintenance of normothermia(ATE:10.9%).Strict adherence to this "care bundle" over the first 72 hours during acute hospital care in patients with ICH was independently associated with improved functional long-term outcome, driven by systolic blood pressure control and maintenance of normothermia. Our findings strongly warrant prospective validation to determine the generalizability especially in western countries.